SISTEM AKUNTANSI PEMBELIAN DAN SISTEM AKUNTANSI UTANG - Asen Devito Hutabarat; Markus Robin Harefa; Rafli Faturrahman (At-Tanmiyah Jurnal Ekonomi dan Bisnis Islam, 2024)
The purchasing accounting system and accounts payable accounting system are essential components in supporting operational efficiency and strengthening internal control within a company. This study aims to describe the procedures of the purchasing accounting system, the accounts payable system, and to evaluate their effectiveness in organizational operations. The analysis is based on theoretical explanations regarding cash purchases, credit purchases, and cash disbursement procedures for settling payables. The results indicate that both cash and credit purchasing systems involve structured processes beginning with inventory requests, managerial authorization, purchase ordering, receipt of supplier documents, and the recording of transactions into the appropriate journals. The accounts payable system follows a sequence of invoice verification, posting into the accounts payable ledger, and controlled payments using checks, which offer greater security in the settlement process. Each procedure is supported by essential documents such as stock requests, purchase orders, invoices, and cash disbursement vouchers, all of which function as internal control instruments. The analysis concludes that both systems comply with internal control principles through segregation of duties, authorization steps, and document completeness, thus enhancing accuracy in recording and timeliness in payment processing. Overall, the purchasing and accounts payable accounting systems are considered effective and efficient in ensuring operational reliability and the accuracy of accounting information. Keywords: purchasing accounting system, accounts payable system, cash purchases, credit purchases, internal control.